A Analisis Kandungan Bahan Kimia Obat Natrium Diklofenak Dalam Jamu Encok - Lisaura, Inggrit Windy; Hastika, Febby Yulia; Manurung, Davidson; Mara, Ignatius Ronaldy; Husnati, Lailan; Bariroh, Laili; Rizantha, M. Iqbal (Jurnal Pelayanan Kefarmasian dan Sains, 2024)
Background: Jamu is a traditional herbal medicine made from natural ingredients, inherited as a cultural heritage passed down from generation to generation for health purposes. The increasing use of jamu has led some producers to add pharmaceutical chemicals (BKO) to their products, which can be dangerous and cause side effects for consumers. Purpose: This study aims to analyze the content of sodium diclofenac in jamu used for joint pain relief. Methods: The research methodology includes a qualitative approach using Thin Layer Chromatography (TLC) and a quantitative approach using UV-VIS Spectrophotometry. Results:  The qualitative analysis using TLC on the jamu pegel linu/encok sample tested positive for sodium diclofenac with an Rf value of 0,87. The quantitative test using UV-Vis spectrophotometry yielded an a value of 0,092, a b value of 0,114, and an r value of 0,993. The concentration of sodium diclofenac in the jamu pegel linu sample was found to be 18,90 ppm. Conclusion: The tested jamu sample for joint pain relief contains sodium diclofenac and is not suitable for distribution.